PENGEMBANGAN SENI PERTUNJUKAN LANGEN MANDRAWANARA SEBAGAI ASET PARIWISATA DI DESA SEMBUNGAN KABUPATEN BANTUL - Kuswarsantyo - (FBS UNY, 2007)
Langen Mandrawanara is one of rare arts, created by Patih Danurejo in the reign of Sultan Hamengkubuwana VIII. Besides its low frequency of performance, the rareness is caused by the difficulties of that dance with Ramayana epic theme. The art of Langen Mandrawanara is performed with squatting and the dialogs are carried out through tembang, traditional Javanese songs. The difficulties make Langen Mandrawanara less interesting to young generation incapable of singing the songs. As the time goes by, efforts are made by art groups and organizations to preserve Langen Mandrawanara, which are good steps to support the art preservation. The one carried out by Langen Mandrawanara community in Sembungan Village, Bangunjiwo, Bantul becomes the key to the future of the art. The endeavor also becomes an appeal to the tourists. The application of pseudo traditional arts is quite relevant as an attempt to keep Langen Mandrawanara art improving, without neglecting its essential aspects to be preserved. Using a dynamic concept of performance, Langen Mandrawanara is hoped to attract the viewers, especially of the young generation. Key words: Langen Mandrawanara, preservation, tourism